Framing the Faithful: Islam, Gender, and National Identity on the Indonesian Screen - Anas Ahmadi; Mohd Adi Amzar Muhammad Nawawi; Kamal Yusuf; Saiful Hadi; Moh. Hafid Effendy; Mohammad Turhan Yani (KARSA Journal of Social and Islamic Culture, 2025)
The study of masculinities in the context of film is currently attracting global attention from researchers. However, there are still a few researchers who study Muslim men as heroes in the context of Indonesian films. In this regard, this research aims to explore Muslim male heroes in Indonesian horror and silat films through the perspective of masculinity. This research employs qualitative methods, with data collection techniques conducted through a literature review. The data used were Indonesian horror and silat films from 1970 to 2020. The results of this study reveal the following key findings. The results of this study show the following findings. First, in Indonesian horror films, there is a type of male Muslim hero who performs exorcism of demons that possess human bodies; performs exorcism of demons that disturb and cause terror to families/citizens; and fights against black magic shamans. Second, in Indonesian silat films, the type of Muslim male hero is often depicted as a tough, strong, and mighty figure, fighting against the Dutch colonizers. Third, Muslim male heroes who appear in Indonesian films, both horror and silat, are not fully the main hero character. Globally, this research is expected to contribute to Islamic studies on male heroes in films from the perspective of masculinity, a topic that has been rarely explored in Islamic studies.